Rethinking Development Communication: Integrating Linguistics, Arts, and Education in a Globalized World - Julien Moreau (Britain International for Academic Research (BIAR) Publisher, 2009)
In the context of accelerating globalization, development communication has evolved beyond its traditional focus on information dissemination to encompass linguistic diversity, artistic expression, and educational transformation. This study examines how development communication is reshaped through the intersections of language, media arts, and education in contemporary global settings. Drawing on an interdisciplinary framework, the research explores how linguistic practices such as multilingualism, translation, and digital discourse contribute to the accessibility and effectiveness of communication strategies. At the same time, artistic media—including film, visual storytelling, and digital content—are analyzed as creative tools that enhance audience engagement and cultural representation. From an educational perspective, development communication is increasingly positioned as a means of fostering critical literacy, intercultural competence, and participatory learning. The study employs a qualitative descriptive approach based on literature review and thematic analysis of global communication practices across diverse socio-cultural contexts. The findings reveal that effective development communication in a globalized era requires the integration of linguistic sensitivity, creative media practices, and inclusive educational strategies. Furthermore, the study highlights the importance of balancing global communication models with local cultural identities to ensure relevance and sustainability. This research contributes to the growing discourse on interdisciplinary approaches to communication by emphasizing the role of language, arts, and education in shaping more inclusive, adaptive, and culturally responsive development practices in a globalized world.